Managing plant genetic diversity - Engels, J.M.M.; Ramanatha Rao, V.; Brown, A.H.D.; Jackson, M.T. (2002)
The proceedings of the conference on Science and Technology for Managing Plant Genetic Diversity in the 21st Century. The book contains more than 40 of the papers presented at conference and addresses key scientific and technical aspects of the management of plant genetic resources now and in the future. We consider it essential reading for those working in genetic resources conservation and believe it will also prove invaluable for those conducting research in areas such as plant genetics, breeding, biotechnology and biodiversity.